Impact of mindset priming on entrepreneurial intentions after unemployment - Koster, Wilhelm (Graduate School of Business (GSB), 2025)
The psychological impact of unemployment on risk aversion suggests that investment in education to increase entrepreneurial intentions amongst unemployed workers is unlikely to succeed without addressing this aversion first. Recent studies in construal level suggest that abstract thinking can reduce risk aversion. Furthermore, mindset theory of action phases research shows that people in an implemental mindset viewed risk factors more positively than people in a deliberative mindset. Based on this premise, this research study tests the impact of mindset of action phases and construal level theory on the retraining choice and entrepreneurial intentions of unemployed workers. Recently unemployed workers were identified from the database of a large retail bank in Southern Africa. We experimentally manipulated the mindset of 144 respondents using a well- known priming technique, and then gave a choice of entrepreneurial or general training. Participants also completed measures of entrepreneurial intention, attitude toward entrepreneurship, and construal level disposition. After confirming construct reliability and discriminant validity, statistical hypothesis tests were utilised to analyse the data. The study results show that implemental (concrete) mindset priming increases the probability of choosing entrepreneurial retraining when attitude toward entrepreneurship is high, and conversely that deliberative (abstract) mindset priming increases the probability of choosing entrepreneurial retraining when attitude toward entrepreneurship is low. In addition to adding to entrepreneurial intention, construal level theory, and mindset theory of action phases literature, this research can help policy makers and intuitions maximise investments in entrepreneurship by improving the take-up of entrepreneurial training by recently unemployed individuals.